2014
DOI: 10.1103/physreva.89.053832
|View full text |Cite|
|
Sign up to set email alerts
|

Resonant-state expansion applied to planar waveguides

Abstract: The resonant state expansion, a recently developed method in electrodynamics, is generalized here to planar open optical systems with non-normal incidence of light. The method is illustrated and verified on exactly solvable examples, such as a dielectric slab and a Bragg reflector microcavity, for which explicit analytic formulas are developed. This comparison demonstrates the accuracy and convergence of the method. Interestingly, the spectral analysis of a dielectric slab in terms of resonant states reveals a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 28 publications
0
57
0
Order By: Relevance
“…The formalism of RSs has been recently applied to a uniform planar WG, and all types of RSs, including WG, anti-WG, and FP modes were calculated for an infinitely extended dielectric slab surrounded by vacuum [2]. It has also been shown that in spite of their exponential growth outside the WG, unbound RSs naturally discretize the continuum of radiation modes and are suited for expansion of the EM field inside the WG.…”
Section: Formulation Of Wg-rsementioning
confidence: 99%
See 4 more Smart Citations
“…The formalism of RSs has been recently applied to a uniform planar WG, and all types of RSs, including WG, anti-WG, and FP modes were calculated for an infinitely extended dielectric slab surrounded by vacuum [2]. It has also been shown that in spite of their exponential growth outside the WG, unbound RSs naturally discretize the continuum of radiation modes and are suited for expansion of the EM field inside the WG.…”
Section: Formulation Of Wg-rsementioning
confidence: 99%
“…The RSE calculates RSs of a given optical system using RSs of a basis system which is typically analytically treatable, as a basis for expansion, and maps Maxwell's wave equation onto a linear matrix eigenvalue problem. This approach has been applied to uniform WGs [2] for the case of a fixed real in-plane propagation wavevector. For the description of propagation along a waveguide, we consider here instead RSs for a fixed real frequency, having in general complex in-plane wavevectors, and use them to formulate a fixed-frequency RSE for homogeneous parts of WGs.…”
Section: Formulation Of Wg-rsementioning
confidence: 99%
See 3 more Smart Citations